Four new sesquiterpenoids from Dendranthema morifolium (Ramat.) kitam flowers. (February 2018) - Chen, Wenjing; Zeng, Mengnan; Li, Meng; Li, Fang; Zhao, Xuan; Fan, Hui; Zheng, Xiaoke; Feng, Weisheng
Graphical abstract: Highlights: Sesquiterpenoids were isolated from Dendranthema morifolium (Ramat.) kitam flowers. Their structures were determined by extensive spectroscopic analyses. Compounds 2 and 5–8 exhibited anti-inflammatory effects against LPS-induced inflammatory. Abstract: Four new sesquiterpenoids, chrysanthguaianolactones C-F (1–4), together with four known sesquiterpenoids (5–8), including 3α, 4α, 10 β -trihydroxy- 8α-acetoxyguai-1, 11(13)-dien-6α, 12-olide (5), 3α, 4α, 10 β -trihydroxy-8α-acetoxy −11 β H-guai-1-en-12, 6α-olide (6), 8α-(angelyloxy)-3 β, 4 β- dihydroxy-5αH, 6 β H, 7αH, 11αH-guai-1(10)-en-12, 6-olide (7) and 3 β, 4α-dihydroxy-8α-angelyloxy-1(10), 11(13) −dien-6α, 12-olide (8) were obtained from an ethyl acetate fraction, which was yielded from an acetone extract of Dendranthema morifolium (Ramat.) kitam. Their structures were determined with extensive spectroscopic (UV, IR, HR-ESI–MS, and 1D and 2D NMR) analyses. In addition, compounds 1–8 were evaluated for their anti-inflammatory effects on H9c2 cardiocytes impaired by lipopolysaccharide (LPS). Among them, compound 2 and compounds 5–8 exhibited anti-inflammatory effects against LPS-induced inflammation.